Predictive ESO-based control with guaranteed stability for uncertain MIMO constrained systems. (June 2021) - Castillo, Alberto; Santos, Tito L.M.; Garcia, Pedro; Normey-Rico, Julio Elias
Abstract: In this paper, a novel predictive Extended State Observer (ESO)-based discrete controller with guaranteed input-to-state stability is developed. Predictive controllers based on ESOs are gaining acceptance for regulating MIMO systems with disturbances, uncertainties or actuator constrains. However, there is an important concern about this control structure regarding its closed-loop stability; a key property that is not strictly guaranteed with the most part of the previous formulations. This paper shows that –under the same assumptions that are normally taken in the ESO literature– a predictive ESO-based controller that is proved to be input-to-state stable can be easily constructed by adding two fixed terms in the cost-index definition. A simulation case study of the glucose control in patients with type-1 diabetes is additionally given in order to illustrate the main advantages of this control structure. Highlights: A novel predictive ESO-based controller with guaranteed stability for uncertain constrained MIMO systems is proposed. Stability is guaranteed due to the insertion of two fixed elements in the cost-index. The stability is proved under the same assumptions than the ones normally taken in the ESO literature. Comparisons with respect to the GESOBC are established. A comparative simulation for glucose control in patients with type-1 diabetes is included.